The practice of strategy: South African defence in stasis. Issue 1 (2nd January 2018) - Esterhuyse, Abel; Louw, Gerhard
ABSTRACT: The article concerns the strategy development processes of the South African Department of Defence in South Africa. It intends to identify the probable causes of the observed failure of the South African National Defence Force to develop appropriate departmental policy and military strategy. Military strategy comprises force development, force employment, force deployment and the coordination of these elements in pursuit of national, grand-strategic objectives. (See Dennis M. Drew and Donald M. Snow, Making Twenty-first Century Strategy: An Introduction to Modern National Security Processes and Problems Montgomery, AL: Air University Press, Maxwell Air Force Base, November 2006, 103). Of these four constructs, the article concerns itself only with the first two. The article analyses two complementary approaches to strategy formation: a resource-driven, inside-out model and an interests-driven, outside-in method. The article concludes that the Department is preoccupied with the inside-out method to the lasting detriment of the declared strategic intent of the defence policy.